2003
DOI: 10.1021/ac034878v
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Analytes Formed from Arsenosugars:  Determination by HPLC−HG-ICPMS and Implications for Arsenic Speciation Analyses

Abstract: It is generally accepted that the use of the hydride generation method to produce volatile analytes from arsenic compounds is restricted to the two inorganic forms (As(III) and As(V)) and the three simple methylated species methylarsonate (MA), dimethylarsinate (DMA), and trimethylarsine oxide. We report here that arsenosugars, major arsenic compounds in marine organisms, produce volatile analytes by the hydride generation (HG) method without a prior mineralization/oxidation step and that they can be quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…An aqueous 0.02 mol L -1 NH 4 H 2 PO 4 solution (pH 6.0) at a flow rate of 1.5 mL min -1 served as mobile phase. The column effluent was introduced into the plasma of the ICPMS (Agilent 4500) for As selective-detection [22]. [7] in liquid cultivation medium, was not confirmed.…”
Section: Methodsmentioning
confidence: 98%
“…An aqueous 0.02 mol L -1 NH 4 H 2 PO 4 solution (pH 6.0) at a flow rate of 1.5 mL min -1 served as mobile phase. The column effluent was introduced into the plasma of the ICPMS (Agilent 4500) for As selective-detection [22]. [7] in liquid cultivation medium, was not confirmed.…”
Section: Methodsmentioning
confidence: 98%
“…The speciation analysis of arsenic in seaweeds has made progress recently, 17,28) and consequently some AsSugs (dimethylarsinoyl ribose derivatives) have been identified as major organic arsenics in seaweeds. [29][30][31] Shibata et al 29) reported that AsSug 408 was the major, AsSug 392 was the minor, and AsSug 482 and 391 were the trace constituents in Hijiki fusiforme. AsSug 482 was not determined in our samples of #8.…”
Section: Discussionmentioning
confidence: 99%
“…Almela 8) and Raab et al 9) reported the concentrations of AsSug 328, 392, 408 and 482 in water extracts of hijiki products. Schmeisser et al 30) reported the detection of the four AsSugs in hijiki and that the content of As-Sug 408 was the highest at 11.3 mg As/kg. This value is very similar to our samples (samples #6-9) produced in the Boso area.…”
Section: Discussionmentioning
confidence: 99%
“…An aqueous 0.02 mol L -1 NH 4 H 2 PO 4 solution pH 6.0 at a flow rate of 1.5 mL min -1 served as mobile phase. The column effluent was introduced into the plasma of the ICPMS (Agilent 7500) for arsenic selective-detection [36].…”
Section: Chromatographic Systemsmentioning
confidence: 99%